2022
DOI: 10.1017/s0959774321000639
|View full text |Cite
|
Sign up to set email alerts
|

Neolithization and Population Replacement in Britain: An Alternative View

Abstract: Investigation of British Mesolithic and Neolithic genomes suggests discontinuity between the two and has been interpreted as indicating a significant migration of continental farmers, displacing the indigenous population. These incomers had already acquired some hunter-gatherer genetic heritage before their arrival, and this increased little in Britain. However, the proportion of hunter-gatherer genetic ancestry in British Neolithic genomes is generally greater than for most contemporary examples on the contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…It is also interesting to note that Britain and Ireland buck the wider European trend of a WHG 'resurgence'. This could either be because Neolithisation processes were more disruptive in these island settings than elsewhere, or because such admixture had taken place during an archaeologically quite poorly documented pioneer phase, as recently argued by Julian Thomas (2022). This is a question that can only be solved through further targeted archaeological work, including the precise dating of any overlap between huntergatherer and farmer lifeways (e.g.…”
Section: Problems With Archaeogenetic Narrativesmentioning
confidence: 97%
See 2 more Smart Citations
“…It is also interesting to note that Britain and Ireland buck the wider European trend of a WHG 'resurgence'. This could either be because Neolithisation processes were more disruptive in these island settings than elsewhere, or because such admixture had taken place during an archaeologically quite poorly documented pioneer phase, as recently argued by Julian Thomas (2022). This is a question that can only be solved through further targeted archaeological work, including the precise dating of any overlap between huntergatherer and farmer lifeways (e.g.…”
Section: Problems With Archaeogenetic Narrativesmentioning
confidence: 97%
“…As has repeatedly been criticised (e.g. Frieman and Hofmann 2019;Furholt 2021;Hofmann 2015;Thomas 2022) we are being presented with models of single, directed and large-scale migrations involving the meeting of two previously separate populations -but each link in this chain can be questioned. Settling not just the 'what' happened (people moved), but also the 'why, how and when' questions, requires substantial amounts of data -isotopic, chronological, archaeological and more -and the testing out of different models and scenarios.…”
Section: Problems With Archaeogenetic Narrativesmentioning
confidence: 99%
See 1 more Smart Citation
“…
I dedicate this article to the memory of Caroline Wickham-Jones (1955-2022, an outstanding archaeologist and inspiration to Mesolithic studies and to me personally for more than 30 years.Ancient DNA studies have identified western Scotland as the only known region in Britain where inter-breeding occurred between early 4th millennium BC Neolithic migrants and the indigenous Mesolithic population. By drawing on excavations at Mesolithic and Neolithic sites on the Isle of Islay, I identify a period of population overlap and suggest three scenarios for Mesolithic-Neolithic interaction: swift succession, dual population, and biocultural merger.
…”
mentioning
confidence: 99%
“…I dedicate this article to the memory of Caroline Wickham-Jones (1955-2022, an outstanding archaeologist and inspiration to Mesolithic studies and to me personally for more than 30 years.…”
mentioning
confidence: 99%